The theoretical bases of the study of color lexicon in linguistics (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
A number of controversial issues that revolve around kolorativov, are the reason that the names of colors over the last few decades have been the subject of constant interest of linguists who study the problem of semantics. The paper discusses the theoretical basis of the research tsvetonaimenovany in Ukrainian language, East Slavic linguistics. Various aspects of classification and analysis kolorativov.
Keywords: kolorativ; tsvetonaimenovanie; the color; the semantics of token; the theme group